2007
DOI: 10.1016/s0377-1237(07)80004-9
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis B e Antigen Negative Chronic Hepatitis in Indian Patients : A Reality

Abstract: Background: Hepatitis B e antigen negative chronic hepatitis (e -CHB) with detectable levels of hepatitis B virus DNA (HBV DNA) in serum has been reported in cases from Asia. This study was undertaken to find out prevalence e -CHB and to correlate its presence with the clinical status and severity of the illness in cases of chronic liver disease in India.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 13 publications
1
5
0
Order By: Relevance
“…These groups of patients are mostly asymptomatic and study also revealed that asymptomatic subjects with incidental detection of hepatitis B surface antigen (HBsAg),usually have a benign non- 15 progressive course . In our study majority of patients were in HBeAg negative chronic infection 66.4% (s79) not requiring treatment, similar observation was also reported by 8 Balasubramanian et al In this group of patients were having normal bilirubin, normal ALT and low or undetected HBV DNA 9 level comparable to other study also . So in this group of patients, no need of antiviral therapy unless significant fibrosis detected by liver biopsy or other non-invasive tests.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…These groups of patients are mostly asymptomatic and study also revealed that asymptomatic subjects with incidental detection of hepatitis B surface antigen (HBsAg),usually have a benign non- 15 progressive course . In our study majority of patients were in HBeAg negative chronic infection 66.4% (s79) not requiring treatment, similar observation was also reported by 8 Balasubramanian et al In this group of patients were having normal bilirubin, normal ALT and low or undetected HBV DNA 9 level comparable to other study also . So in this group of patients, no need of antiviral therapy unless significant fibrosis detected by liver biopsy or other non-invasive tests.…”
Section: Discussionsupporting
confidence: 90%
“…Majority of patients were in the age group of 30-60 years 51.3% (61). Balasubramanian et al also reported male preponderance in their study with mean age of men was 40 years and of women 8 was 34 years . Shrestha SM et al, in their prevalence study also reported male predominance but highest prevalence of CHB infection among age groups of 6-15 years compared to 30-60 5 years in our study The difference in age group might be explained as our was hospital based study, serological test for HbsAg only done when indicated as compared to their community based prevalence study.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…Detection of HBV-DNA was carried out by in-house qualitative polymerase chain reaction (PCR) amplifying the 5-prime end of pre-core and core regions of the HBV genome (nucleotide positions 1730-2388) using assay steps described previously by Lahiri et al 21 Briefly, the PCR primers used were primer 1 (forward) 5′-CTG-GGA-GGA-GTT-GGG GGA-GGAGAT-T-3′ and primer 2 (reverse) 5′-GGC-GAG-GGA-GTT-CTT-CTT-CTAGGG-G-3′. The PCR cycling conditions were as follows: Initial denaturation at 94°C, followed by 30 cycles of denaturation (94°C × 1 minute), primer annealing (50°C × 1 minute), extension (72°C × 2 minutes), and final extension at 72°C × 7 minutes.…”
Section: Methodsmentioning
confidence: 99%
“…In another article published in this journal, Lahiri et al [12] have reported that HBeAg negative chronic hepatitis B is present in upto 8.3% of patients with chronic hepatitis B virus infection. HBeAg and HBV-DNA are markers of replication of HBV.…”
Section: H Epatitis B Virus (Hbv) Infection Is a Health Problemmentioning
confidence: 99%